Analysis on deformation characteristics of geological hazards in Ranwu Lake Estuary - Zhinan ZHAO; Bin LI; Yang GAO; Chaoying ZHAO; Xiaojie LIU; Meng WANG (Zhongguo dizhi zaihai yu fangzhi xuebao, 2021)
The continuous uplift of the Qinghai Tibet Plateau has led to frequent geological disasters in its surrounding areas. The complex geological background has created the characteristics of chain disaster development and high risk of river blocking in the Palongzangbu basin. In recent years, Ranwu Lake estuary, located in the Palongzangbu basin, has experienced severe geological deformation. In this paper, the risk material sources identification in 82 road class at Ranwu Lake are carried out by optical remote sensing and InSAR monitoring technology. It can be found that there are four risk source types in the study area: high-level ice debris, collapse, moraine and avalanche. Characteristics analysis and disaster risk assessment are carried out for each risk source, and based on the geological background of Ranwu Lake, this paper expounds the disaster causing factors and modes of risk material sources. Combined with the InSAR monitoring results. The slope body and its upper interpretation risk material sources areas on the right bank of Ranwu Lake estuary are divided into three high risk areas: 82 road class, Polong and Yalong, and the deformation characteristics are analyzed.